Risk-Based Multi-Objective Cross-Asset Budget Planning and Allocation Framework for the City of Sugar Land Integrated Asset Management System (IAMS). (January 2022) - Poudel, Alence; Damnjanovic, Ivan; Van Tang, Quynh; Valenzuela, Robert
An Integrated Asset Management System (IAMS) is a strategic asset management system that combines the assets of different categories into a system to prioritize their maintenance. This paper proposes a risk-based reliability-centric IAMS framework which works on the principle that the risk associated with the failure of an asset is a function of its direct and indirect costs. The direct costs are the costs associated with the replacement of the assets, whereas the indirect costs are the risks that the city faces following the failure. The framework is applied to the asset database of the City of Sugar Land, TX. The results of the model are analyzed in terms of a reduction in the number of assets in a very high-risk category in the risk matrix, the network level expected annual failure rate, and an increase in the network level average reliability.